Déficit hídrico em estágios fenológicos no cultivo de cártamo - Daniel, Cintia (2022)
Safflower is an oilseed crop belonging to the Asteraceae family, which has recently received attention from scientific works that recognize the quality of the oil extracted and the resistance of the crop in dry and cold regions. However, it is known that, even in the case of a crop that grows in dry environments, it has an increase in productivity when cultivated in irrigated areas. Thus, the objective of this work was to evaluate the water stress indices in the safflower crop, using the replacement of water in the soil with the use of the evaporimeter, and to determine the stages of greater water demand. The study was divided into two stages: an experiment conducted in a greenhouse and another carried out in the field. Both studies were conducted in the city of Cascavel-PR, using a completely randomized experimental design (DIC), consisting of eight treatments. Treatments consisted of irrigation at different stages of crop development. The analyzed variables were: plant height, stem diameter, fresh and dry mass of shoots, number of chapters, number of seeds and weight of seeds. In the study conducted in a greenhouse, the plant height parameter had the lowest average when it did not receive any irrigation. According to ANOVA, for the stem diameter parameter, the treatments did not show significant differences between them. Fresh and dry mass were more sensitive to water deficit when irrigated only in the reproductive and grain formation stages. The smallest number of capitula was evidenced in the treatment that did not receive any irrigation. The parameters number of seeds and seed weight presented negative results in the irrigated treatments only in the vegetative and grain formation, reproductive and grain formation stages, all stages and the one that did not receive any irrigation. In the experiment carried out in the field, the parameters plant height and stem diameter were more sensitive in the treatments that did not receive any irrigation. The number of chapters did not show significant differences between their treatments. For the ix parameters fresh and dry mass, number of seeds and weight of seeds, the treatment that had irrigation available in all stages showed a significant drop in their averages. In conclusion, it was found that water scarcity, due to irrigation restriction during the vegetative phase, reduces the morphological components of safflower. The availability of water, only in the reproductive and grain formation stages, results in a decrease in the biomass components, and safflower productivity is favored when irrigated in the vegetative and reproductive stages of the crop.